2017
DOI: 10.4103/ijdr.ijdr_13_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of at-home and in-office bleaching agents on the shear bond strength of metal, ceramic, and composite brackets to enamel

Abstract: The results showed that at-home bleaching did not affect the SBS significantly whereas in-office bleaching reduced SBS of metal, ceramic, and composite brackets significantly. It is preferable to use metal or ceramic brackets than composite brackets for bonding 24 h after bleaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The specimens that were not treated with any bleaching gel showed similar results to the bleached specimens. Conversely, an in vitro study reported that office bleaching treatment with 40% HP reduced SBS values but home bleaching treatment with 10% CP had no effect [ 24 ]. However, the adhesives were applied after 1 day in that study.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens that were not treated with any bleaching gel showed similar results to the bleached specimens. Conversely, an in vitro study reported that office bleaching treatment with 40% HP reduced SBS values but home bleaching treatment with 10% CP had no effect [ 24 ]. However, the adhesives were applied after 1 day in that study.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth emphasizing that significantly higher values of SBS for ceramic brackets in comparison to those for metal ones in both etching protocols were observed. However, the literature's findings are ambiguous regarding this issue [6,[26][27][28][29][30][31][32][33]. The majority of studies have confirmed the advantage of ceramic brackets over metal ones in terms of the SBS value [6,[26][27][28][29][30] (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature's findings are ambiguous regarding this issue [6,[26][27][28][29][30][31][32][33]. The majority of studies have confirmed the advantage of ceramic brackets over metal ones in terms of the SBS value [6,[26][27][28][29][30] (Table 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for a high adhesion of the brackets to the dental tissue is essential to withstand the orthodontic forces and allow the control of the tooth movements [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%